THE EFFECT OF PRAISE-QUESTION-POLISH (PQP) STRATEGY ON STUDENTS’ WRITING DESCRIPTIVE TEXT OF THE TENTH GRADE STUDENTS OF SMA SWASTA YPIS MAJU BINJAI - Ummi Umara (Jurnal Serunai Bahasa Inggris, 2019)
Based on School Based Curriculum, writing is one of the English language  skills that must be taught and learned in Senior High School. SMA Swasta YPIS Maju Binjai is a school which uses K13 as the curriculum in the teaching and learning process. After doing observation in SMA Swasta YPIS Maju Binjai, the writer found that the students were difficult in developing a descriptive text. In this case, the teacher was expected to find a good strategy in order to give a contribution to increase the students’ ability in writing a descriptive text by applying Praise-Question-Polish (PQP) Strategy as a replacement of previous strategy or technique.This research consisted of two variables, they were Praise-Question-Polish Strategy as variable X, and students’ writing descriptive text as variable Y. The type of this research was an experimental research. The writer used a quasi-experimental design with nonequivalent control group which was intended to find out the effect of using Praise-Question-Polish (PQP) Strategy on students’ writing descriptive text of the tenth grade students of SMA Swasta YPIS Maju Binjai.In  analyzing  the  data,  the  writer  used a statistical  analysis  which  used t-table. It was obtained that t-obtained was higher than t-table. It means, null hypothesis (H0) was rejected, and alternative hypothesis (Ha) was accepted. It could be stared that 6,971 > 1,672. In conclusion, there was a significant effect of using praise-question-polish strategy on students’ writing descriptive text of the tenth grade students of SMA Swasta YPIS Maju Binjai.